The forgotten foot – An assessment of foot and ankle radiograph pathology in final year medical students. Issue 5 (October 2015) - Groarke, P.J.; Kelly, J.C.; Flanagan, E.; Stephens, M.M.
Abstract Introduction It has been shown that doctors in Emergency Departments (EDs) have inconsistent knowledge of musculoskeletal anatomy. This is most likely due to a deficiency in focused musculoskeletal modules at undergraduate level in medical school. The aims of this study were to evaluate the knowledge of final year medical students on foot anatomy and common foot and ankle pathology as seen on radiographs. Methods Final year medical students were asked to complete our short examination on a handout. The handout was anonymous and non-mandatory. There were four images. The first image is the anatomical section and the remaining images are the pathological section. Results All 235 students responded. 57% were females. For the identification of the normal bones of the foot as shown on an X-ray, the average score for the group was 2.69 (out of a maximum of 6) {SD 1.67}7. Only 8.3% achieved a 6/6 or 100% grade i.e. recognising all six bones correctly. A further 8.3% achieved 5/6 (83%). 8.3% failed to correctly identify any bone seen on the X-ray, a corresponding score of 0. Discussion This quick test showed normal anatomy of the foot and common pathology. One would expect final year medical students to be familiar with, especially two weeks before their finals in surgery. The curriculum should address the paucity of time spent in educating students in foot and ankle pathology.